2020
DOI: 10.1002/ente.202000535
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Swirl‐Induced Rotating Glow Discharge Reactor for CO2 Conversion: Fluid Dynamics and Discharge Dynamics Studies

Abstract: Herein, CO2 conversion is conducted in a newly developed swirl flow–induced rotating glow discharge reactor. The swirl injector is designed to produce forward vortex by eight inclined guided vanes. A glow‐type rotating discharge is formed between two electrodes of constant height. The discharge and fluid dynamics studies reveal that the magnitude of tangential velocity and secondary vortex formation affects the rotational frequency of the discharge. It is also found that the anchoring point of the plasma colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…These vanes were mounted on a central hub of 20 mm diameter. Our previous work on CO 2 dissociation to CO and O 2 employed a similar swirl injector, but a ring electrode was employed instead of a point electrode used in this study . Initial experiments using the ring electrode suggested that carbon channelling occurred in between the ring electrode and swirl electrode as a result of the cracking of methane gas.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These vanes were mounted on a central hub of 20 mm diameter. Our previous work on CO 2 dissociation to CO and O 2 employed a similar swirl injector, but a ring electrode was employed instead of a point electrode used in this study . Initial experiments using the ring electrode suggested that carbon channelling occurred in between the ring electrode and swirl electrode as a result of the cracking of methane gas.…”
Section: Methodsmentioning
confidence: 99%
“…The present swirl injector has S = 0.9, which ensures the formation of the CRZ. On the basis of the limitation of machinability, swirl number requirement, and central recirculation zone size, the vane angle and number of slots were designed, which are detailed elsewhere . Carbon channelling hinders the rotation of the arc and leads to short circuiting of the electrode gap without any plasma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of reactor designs already in use for CO 2 splitting (the most popular application), a tubular design using vortex flow was presented in 2019 by Trenchev et al [75] Just recently, Raja et al used a vortex gas flow and ring electrodes to prevent arc formation. [76] In a design, which will be further pursued for CHEMampere, collaborators of the initiative have presented a reactor using pin-discharge and an axial magnetic field, [77] which does not utilize a vortex flow and can thus be operated at arbitrary gas flow rates.…”
Section: Dc-glow Dischargesmentioning
confidence: 99%
“…[75] Raja et al also used a vortex gas flow, but ring electrodes to prevent arc formation, being rewarded with a high energy efficiency of 60% at conversions ranging from 2% to 3%. [76] In a design that will be further pursued for CHEMampere, a reactor using pin-discharge and an axial magnetic field was presented, which achieved 27% energy efficiency at 17% conversion. [77] It does not utilize a vortex flow and can thus be operated at arbitrary gas flow rates.…”
Section: Evaluation Of the Technologiesmentioning
confidence: 99%